Experimental study on horizontal frost heave force on open-cut tunnels in seasonal frozen regions - Meng-Ya, Zhang; Hong-Yi, Liu; Li-Dong, Yang; Xing-Zhou, Li; Zi-Hao, Wang; Tang-Dai, Xia (Frontiers in Earth Science, 2023)
Model tests were performed with different temperature and soil stabilizers to investigate the effect of horizontal frost heave force on open tunnels in seasonal frozen regions. Experimental results show that the dissipation of the frost heave force accelerated with the increase in temperature, and the data indicate that compared with soil without stabilizers, the horizontal frost heave force decreased by 10% and 15% in soil with lignin fiber and Huaxia No.1 soil stabilizer. It can be concluded that the inhibitory effect of Huaxia No.1 soil stabilizer on frost heave force was more significant than that of lignin fiber. According to the test results, the relation expression between horizontal frost heave force and frost heave amount was fitted.